Efeitos do treinamento autógeno na atividade cerebral e sobre a ansiedade em indivíduos com altos níveis ansiogênicos - Santos, José Anderson Galdino (2018)
Anxiety has an important role for the species, its presence is necessary for the survival of the individual, assuming the role of defense and preservation, but at high levels causes cognitive and social deficits for those who experience it. The emergence of meditative techniques and relaxation appear as therapeutic possibilities for reducing anxiety levels. Among the most diverse techniques, Schultz's Autogenic Training (TA) emerges as a practical, versatile and inexpensive modality to reduce anxiety and promote a state of well-being. Its applicability to any individual makes it a known practice. The first theoretical study had as objective to carry out a bibliographic survey of studies in the last ones that approach the applicability of the technique for reduction of anxiety The second empirical study, had as objective to verify the effect of the intervention in anxious individuals, observing changes perceived by an anxiety scale and electrophysiological activity through the EEG. Observed a literature that points to the effectiveness of the technique for reduction of anxiety levels and the data of the empirical study noticed changes in the anxiety scores, reducing their perceived levels and the analysis of the electrophysiological activity observed the activation of areas implicated in emotional and attentional processes present in meditative practices. The results of the empirical study suggest that the individuals submitted to the TA presented a significant reduction of the scores on the anxiety scale and presented activation of specific brain regions. It is concluded that TA consists of a technique that may be indicated to provide reduction of anxiety levels.